Mobile Learning Application for Helping Pupils in Learning Chemistry - Ewais, Ahmad; Hodrob, Rami; Maree, Mohammad; Jaradat, Sirien (International Journal of Interactive Mobile Technologies (iJIM), 2021)
Elementary school pupils can face different difficulties to learn different topics. Among the different topics, learning chemical elements and their different properties and interactions. A way to make the learning process easier and effective is using mobile learning. Mobile learning can contribute a new method to educate pupils different topics. Also, mobile learning has different advantages over classical learning materials. Among the different advantages of using mobile learning is the fact that it enables pupils to interact with learning materials, visualize different learning concepts, and learning anytime and anywhere. This article presents an exploration study related to investigating the possible use of educational mobile App to learn chemistry course in elementary school. The article presents also a qualitative research methodology implemented by including 7 pupils. The findings of this research show that mobile learning technology can be adopted for learning chemistry course in order to enable pupils to understand periodic table, chemical elements properties and their chemical interaction. Also, this study has shown that the proposed mobile application can be integrated in learning chemistry course for elementary school pupils.